Japan Trench event stratigraphy: First results from IODP giant piston coring in a deep-sea trench to advance subduction zone paleoseismology - Michael Strasser; Ken Ikehara; Charlotte Pizer; Takuya Itaki; Yasufumi Satoguchi; Arata Kioka; Cecilia McHugh; Jean-Noel Proust; Derek Sawyer; J. Everest; L. Maeda; K. Hochmuth; et al. (Marine Geology, 2024)

The increasing threat to European forests from the invasive foliar pine pathogen, Lecanosticta acicola - K. Tubby; K. Adamčikova; K. Adamson; M. Akiba; I. Barnes; P. Boroń; H. Bragança; T. Bulgakov; N. Burgdorf; P. Capretti; T. Cech; M. Cleary; et al. (Forest Ecology and Management, 2023)

Guidelines on reporting treatment conditions for emerging technologies in food processing - Vicente M. Gómez-López; Gianpiero Pataro; Brijesh Tiwari; Mario Gozzi; María Ángela A. Meireles; Shaojin Wang; Buenaventura Guamis; Zhongli Pan; Hosahalli Ramaswamy; Sudhir Sastry; Florent Kuntz; Patrick J. Cullen; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A tsunamigenic delta collapse and its associated tsunami deposits in and around Lake Sils, Switzerland - Valentin Nigg; Stephan Wohlwend; Michael Hilbe; Benjamin Bellwald; Stefano C. Fabbri; Gregory F. de Souza; Florian Donau; Reto Grischott; Michael Strasser; Flavio S. Anselmetti (Natural Hazards, 2021)
Large lacustrine mass movements and delta collapses are increasingly being considered as potential tsunamigenic sources and therefore hazardous for the population and infrastructure along lakeshores. Although historical reports document tsunami events in several lakes in Switzerland, and although the propagation of lake tsunamis has been studied by numerical wave modeling, only little is known about on- and offshore lacustrine tsunami deposits. In Lake Sils, Switzerland, a large prehistoric mass-movement deposit originating from the Isola Delta with a minimum estimated volume of 6.5 × 10 6 m 3 and a basinal thickness of > 6 m in the seismic record has been identified by previous studies and radiocarbon dated to around 700 Common Era. Here, we combine (i) comprehensive sedimentological investigation of sediment cores recovered from the on- and offshore settings, (ii) mineralogical fingerprinting of the inflows from key catchments to characterize sediment provenance, and (iii) numerical tsunami modeling, to test the hypothesis of a tsunamigenic delta collapse in Lake Sils. We observe a clastic event deposit consisting of coarse-grained, fining-upward sand overlying an organic-rich peat deposit in the shallow water. This layer thins and fines landward on the coastal plain. Toward the deeper water (20–40 m), the deposit transforms into a thicker and more heterogeneous sediment package with multiple sequences of fining-upward sand and a well-pronounced clay cap at the top. Radiocarbon dating of the peat underlying the event deposit yields a maximum age of 225–419 calibrated Common Era. The tsunami models, which indicate wave heights reaching up to 5 m, simulate areas of inundation that coincide with the location of event deposits. Based on our results, we propose that the historically undocumented Isola Delta collapse generated a basin-wide tsunami that inundated the lakeshore, transporting large amounts of unconsolidated sediment along the lakeshore toward the coastal plain and into the deeper lake basin.

Overloaded! Critical revision and a new conceptual approach for snow indicators in ski tourism - B. Abegg; S. Morin; O. C. Demiroglu; H. François; M. Rothleitner; U. Strasser (International Journal of Biometeorology, 2021)
Indicators are widely used in climate variability and climate change assessments to simplify the tracking of complex processes and phenomena in the state of the environment. Apart from the climatic criteria, the snow indicators in ski tourism have been increasingly extended with elements that relate to the technical, operational, and commercial aspects of ski tourism. These non-natural influencing factors have gained in importance in comparison with the natural environmental conditions but are more difficult to comprehend in time and space, resulting in limited explanatory power of the related indicators when applied for larger/longer scale assessments. We review the existing indicator approaches to derive quantitative measures for the snow conditions in ski areas, to formulate the criteria that the indicators should fulfill, and to provide a list of indicators with their technical specifications which can be used in snow condition assessments for ski tourism. For the use of these indicators, a three-step procedure consisting of definition, application, and interpretation is suggested. We also provide recommendations for the design of indicator-based assessments of climate change effects on ski tourism. Thereby, we highlight the importance of extensive stakeholder involvement to allow for real-world relevance of the achieved results.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Epistemological dimensions of the water–energy–food nexus approach: reply to discussions of “Challenges in operationalizing the water–energy–food nexus” - C. Cudennec; J. Liu; J. Qi; H. Yang; C. Zheng; A. K. Gain; R. Lawford; L. de Strasser; P. T. Yillia (Hydrological Sciences Journal, 2018)

Challenges in operationalizing the water–energy–food nexus - J. Liu; H. Yang; C. Cudennec; A.K. Gain; H. Hoff; R. Lawford; J. Qi; L. de Strasser; P.T. Yillia; C. Zheng (Hydrological Sciences Journal, 2017)

Twentieth century seismicity of the Koffiefontein region (Free State, South Africa): consistent determination of earthquake catalogue parameters from mixed data types - F. O. Strasser; P. Albini; N. S. Flint; C. Beauval (Journal of Seismology, 2015)

Uncoupled eNOS annihilates neuregulin-1β-induced cardioprotection: a novel mechanism in pharmacological postconditioning in myocardial infarction - Bernd Ebner; Stefan A. Lange; Thomas Eckert; Clementine Wischniowski; Annette Ebner; Rüdiger C. Braun-Dullaeus; Christof Weinbrenner; Carsten Wunderlich; Gregor Simonis; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2013)

The use of JIP test to evaluate drought-tolerance of transgenic rice overexpressing OsNAC10 - Mark C. F. R. Redillas; Reto J. Strasser; Jin Seo Jeong; Youn Shic Kim; Ju-Kon Kim (Plant Biotechnology Reports, 2011)

A strong-motion database from the Peru–Chile subduction zone - Maria C. Arango; Fleur O. Strasser; Julian J. Bommer; Ruben Boroschek; Diana Comte; Hernando Tavera (Journal of Seismology, 2011)

Increased P2X7R expression in atrial cardiomyocytes of caveolin-1 deficient mice - K. Barth; C. Pfleger; A. Linge; J. A. Sim; A. Surprenant; N. Steinbronn; R. H. Strasser; M. Kasper (Histochemistry and Cell Biology, 2010)

Limited genetic variation and structure in softshell clams (Mya arenaria) across their native and introduced range - C. A. Strasser; P. H. Barber (Conservation Genetics, 2009)

Foodborne outbreak of hepatitis A, November 2007–January 2008, Austria - D. Schmid; R. Fretz; G. Buchner; C. König; H. Perner; R. Sollak; A. Tratter; M. Hell; M. Maass; M. Strasser; F. Allerberger (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Ground motions observed during the 15 August 2007 Pisco, Peru, earthquake - Hernando Tavera; Isabel Bernal; Fleur O. Strasser; Maria C. Arango-Gaviria; John E. Alarcón; Julian J. Bommer (Bulletin of Earthquake Engineering, 2009)

Chelerythrine treatment influences the balance of pro- and anti-apoptotic signaling pathways in the remote myocardium after infarction - Gregor Simonis; Stephan Wiedemann; Kerstin Schwarz; Torsten Christ; Daniel G. Sedding; Xinjian Yu; Rainer Marquetant; Ruediger C. Braun-Dullaeus; Ursula Ravens; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2008)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)

Analysis of mechanisms contributing to AraC-mediated chemoresistance and re-establishment of drug sensitivity by the novel heterodinucleoside phosphate 5-FdUrd-araC - S. Maier; S. Strasser; P. Saiko; C. Leisser; S. Sasgary; M. Grusch; S. Madlener; Y. Bader; J. Hartmann; H. Schott; R. M. Mader; T. Szekeres; et al. (Apoptosis, 2006)

Influence of histamine release on postoperative vomiting (POV) following gynaecological laparoscopic surgery - K. Kimura; D. Rsch; C. Strasser; M. Lengkong; H. Wulf; M. Koller; I. Celik (Inflammation Research, 2004)